Students’ Satisfaction with a Web-Based Pharmacy Program in a Re-Regulated Pharmacy Market - Maria Gustafsson; Sofia Mattsson; Gisselle Gallego (Pharmacy, 2017)
In response to the shortage of pharmacists in Northern Sweden, a web-based Bachelor of Science in Pharmacy program was established at Umeå University in 2003. In 2009, the Swedish pharmacy market was re-regulated from a state monopoly to an open market, but it is unknown what impact this has had on education satisfaction. The objectives of this study were to examine the level of satisfaction among graduates from a web-based pharmacy program and to describe what subjects and skills students would have liked more or less of in their education. A secondary objective was to compare the level of satisfaction before and after the Swedish pharmacy market was re-regulated. A cross-sectional survey was conducted in 2015 with all alumni who had graduated from the pharmacy program between 2006 and 2014 (n = 511), and responses to questions about graduates’ satisfaction with the program were analyzed (n = 200). Most graduates (88%) agreed or strongly agreed that the knowledge and skills acquired during their education were useful in their current job. The graduates stated that they would have wanted more applied pharmacy practice and self-care counselling, and fewer social pharmacy and histology courses. Further, 82% stated that they would start the same degree program if they were to choose again today, and 92% agreed or strongly agreed that they would recommend the program to a prospective student. Graduates were more likely to recommend the program after the re-regulation (p = 0.007). In conclusion, pharmacy graduates were very satisfied with their education, and no negative effects of the re-regulation could be observed on program satisfaction.